Respuesta :

Answer:

Option B is the correct option.

Step-by-step explanation:

Given the expression

[tex]\frac{\sqrt[3]{x^5}}{\sqrt[3]{x^7}}[/tex]

Apply radical rule:

[tex]\frac{\sqrt[n]{a}}{\sqrt[n]{b}}=\sqrt[n]{\frac{a}{b}}[/tex]

so

[tex]\frac{\sqrt[3]{x^5}}{\sqrt[3]{x^7}}=\sqrt[3]{\frac{x^5}{x^7}}[/tex]

Apply radical rule:

[tex]\frac{x^a}{x^b}=x^{a-b}[/tex]

so

   [tex]=\sqrt[3]{\frac{1}{x^2}}[/tex]         ∵  [tex]\frac{x^5}{x^7}=x^{5-7}[/tex]

   [tex]=\frac{1}{x^{\frac{2}{3}}}[/tex]

Therefore, option B is the correct option.